Electronic properties and degradation upon VUV irradiation of sodium chloride on Ag(111) studied by photoelectron spectroscopy. (22nd September 2021) - Wang, Haibo; Oehzelt, Martin; Winkler, Stefanie; Ovsyannikov, Ruslan; Koch, Norbert; Amsalem, Patrick
Abstract: The growth as well as vacuum ultraviolet (VUV) radiation-induced degradation of sodium chloride (NaCl) on Ag(111) is investigated by ultraviolet and x-ray photoelectron spectroscopy. In line with previous scanning tunneling microscopy studies, our results confirm that NaCl grows initially as a bilayer before island growth starts. Simple spectroscopic methods for calibrating the closure of the NaCl bilayer are further presented. In addition, the energy level alignment is studied as a function of NaCl film thickness and VUV-light intensity. When measuring with ultra-low photon flux, a sharp interface dipole lowers the sample work function by 0.65 eV upon adsorption of the first bilayer, which is followed by vacuum level alignment for subsequently deposited layers. In contrast, measurements performed with standard photon fluxes, such as those provided by commercial He discharge lamps, shows 'downward band-bending'-like characteristics in the NaCl films. Upon extended exposure time to the standard VUV intensity, photoemission measurements further reveal that strong modifications of the electronic properties of the NaCl surface occur. These are likely correlated with halogen emission, eventually resulting in the formation of Na clusters promoting low work function of parts of the sample surface. This study provides general guidelines for obtaining reliable spectroscopic measurements on alkali halide thin films on metals.